Characteristics and Precision Analysis of BeiDou2 Satellite Differential Code Bias Products. Issue 3 (19th August 2018) - Wang, Li; Han, Junqiang; Huang, Guanwen; Zhang, Qin; Tu, Rui; Fan, Lihong
Abstract: Currently, resolution of the BeiDou2 satellites differential code bias (DCB) is greatly limited by the number of tracking stations and data quality. To improve the precision of calculated DCBs, an adaptive control method, based on elevation angle weight and posteriori variance factor, is proposed. The feasibility and precision of the proposed method are verified via analysis of the DCBs precision and application of single‐frequency precise point positioning (SF‐PPP). The results show that the long‐term variation of the daily BeiDou2 satellite DCB sequence is stable and the precision of DCBs of BeiDou2 satellites in different constellations is different. In addition, it is found by using periodogram and fast Fourier transform (FFT) methods that weekly and daily periodic signals exist in the daily BeiDou2 satellite DCB products. The results of SF‐PPP show that root mean square (RMS) horizontal residual is reduced by 10% and convergence time is shortened significantly using DCB products. © 2018 Institute of Navigation